Women's empowerment model in increasing economic independence at the community work training center (BLKK) of Lampung Province - Siti Wuryan; Ruslan Abdul Ghofur; M. Mawardi Jafar; Suslina Sanjaya; Rini Setiawati (Universitas Muhammadiyah Malang, 2025)
This study explores the model of women's empowerment based on life skills development to increase economic independence at the Lampung Community Work Training Center (BLKK). Through a life skills-based training program, this study analyzes women's empowerment in increasing economic independence in the Lampung Muslim community. Methodology This study uses a qualitative descriptive approach to understand the model of women's empowerment based on life skills development at the Community Work Training Center (BLKK) in Lampung Province. Data collection was carried out through participatory observation, in-depth interviews, and Focus Group Discussion (FGD) Primary Data Sources Using a purposive sampling technique with Criteria from a Total Number of 73 used according to the Criteria of 11 people, namely 6 participants, 2 instructors, and 2 heads of centers, namely BLKK Pesawaran and BLKK East Lampung and 1 Head of SVP of the Ministry of Manpower Korwil Lampung. In addition, documentation in the form of training modules, activity reports, and evaluation notes is also used as secondary data. The data collected was analyzed using Miles and Huberman's theory, which included data reduction, data presentation, and verification followed by Triangulation. The research data lasted for 3 months, ensuring that the process of empowering women through technical skills training in clothing manufacturing and life skills could be observed comprehensively. The theories used are deliberative empowerment, empowerment of the Madani community, principles of Muslim women's rights, life skills theory, and human capital management (HCM) concept. The results of the study indicate that the deliberative empowerment model at BLKK Lampung is based on deliberation, cooperation, and active participation, supporting the development of participants' life skills, especially sewing, hard skills and communication soft skills, and self-confidence. The application of the principle of women's rights in Islam encourages equality and empowerment in social, economic, and spiritual aspects. The integration of human capital includes increasing human, social, and organizational capital, enriched with Islamic values, providing a comprehensive impact on the economic independence and welfare of participants.